Youth benefit finding and caregiving in a parental illness context: a latent profile analysis - Landi, Giulia; Pakenham, Kenneth I.; Pilato, Jade; Dorard, Géraldine; Untas, Aurélie; Cattivelli, Roberto; Grandi, Silvana; Tossani, Eliana (Frontiers in Psychology, 2025)
IntroductionThis study used a person-centred approach to identify patterns of engagement in benefit finding (BF) and caregiving among youth who have a parent with a serious illness.MethodsA total of 403 youth completed questionnaires in a cross-sectional study.ResultsLatent profile analyses revealed four profiles. The distribution of caregiving and participants across profiles reflected the caregiving continuum. The ‘low BF & caregiving profile’ had the lowest caregiving and the highest proportion of participants at the low end of the continuum, while the ‘moderate BF & extremely high caregiving profile’ had the highest caregiving and the lowest proportion of participants at the high end. The two mid-continuum profiles reflected mid-to-high proportions of caregiving and participants. Results highlighted a corresponding continuum in BF, where engagement varies in sync with caregiving intensity. Profiles differed on demographics, caregiving context, health-related quality of life (HRQoL), and mental health variables. The two mid-continuum profiles reported high caregiving and moderate-to-high BF and evidenced better HRQoL and mental health than the profile at the highest end of the caregiving continuum, but worse HRQoL and mental health than the profile at the lowest end. Despite high caregiving, these two profiles exhibited moderately high HRQoL and mental health, indicating that BF mitigates the adverse impacts of high caregiving. Results also supported the BF theoretical proposal that caregiving must be sufficiently intense to trigger BF.DiscussionSupport services should reduce youth caregiving responsibilities and encourage youth caregivers to explore the positive aspects of their caregiving role.